Pathological Gambling Associated With Aripiprazole or Dopamine Replacement Therapy: Do Patients Share the Same Features? A Review. Issue 1 (February 2016) - Grall-Bronnec, Marie; Sauvaget, Anne; Perrouin, Fanny; Leboucher, Juliette; Etcheverrigaray, François; Challet-Bouju, Gaëlle; Gaboriau, Louise; Derkinderen, Pascal; Jolliet, Pascale; Victorri-Vigneau, Caroline
Abstract : Background: In the last 10 years, dopamine replacement therapy (DRT) has become a well-known risk factor for developing an impulse control disorder, such as gambling disorder (GD). Another medication, aripiprazole (ARI), has been more recently identified as another risk factor. Dopamine replacement therapy and ARI share a dopamine agonist action. Our work aimed at comparing patients with PG according to their treatment with DRT or ARI. Methods: Two methods were combined—a systematic review concentrated on case reports and the analysis of a French disordered gamblers cohort focused on patients using ARI or DRT at inclusion. Results: We reported 48 cases of GD possibly due to DRT and 17 cases of GD possibly due to ARI. Because of their standardized assessment, only the EVALJEU patients could be compared. Two clinical patterns emerged. Patients in the ARI group were young, impulsive, and high novelty seekers and had a history of substance misuse. Their first gambling experience occurred during adolescence. Conversely, patients in the DRT group were old, and they began gambling late in life. They showed low levels of gambling-related cognition. Conclusions: Patients in the ARI group seemed to be more severe pathological gamblers than patients in the DRT group. Aripiprazole is a partial D2 receptor agonist, whereas DRT includes full D2 receptor agonist. The trigger mechanism of PG development is complex and cannot only be attributed only to the pharmacodynamic effects of dopaminergic drugs. Indeed, individual vulnerability factors and environmental factors need to be considered. Abstract : Supplemental digital content is available in the text.